Senam Birth Ball dalam Mengatasi Nyeri pada Persalinan Kala I - Deby Utami Siska Ariani (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2024)
Physiologically, pain is generally felt by all mothers who face the birth process. Pain arises due to uterine contractions which are useful for opening the cervix. However, intense pain can disturb comfort and can affect psychological conditions. As many as 46% of primigravida mothers experienced severe pain, 64% experienced mild to moderate pain. In multigravida mothers, 37% experienced severe pain and 63% experienced moderate and mild pain. One way to overcome severe pain in the first stage is birth ball exercises. The aim of the research was to determine the effect of using a birth ball on first stage labor pain. The design of this research was a quasi-experimental one group with control group. The population in this study were all mothers giving birth at PMB Dewi Anggraini in March-April 2024, totaling 28 respondents. The sampling technique used is total sampling. Statistical tests use the Independent Sample T Test. The average pain in the intervention group was 3.52 and the average labor pain in the control group was 5.52, meaning there was a reduction in pain levels of 2.00. The significant value was found to be p: 0.001 < 0.05, meaning that there was a difference in the pain scale of the first stage of labor in the groups that used a birth ball and those that did not use a birth ball. It is hoped that health workers can improve maternal care during childbirth, one of which is by inviting mothers to use a birth ball.